If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) = 2(x + 6) Reorder the terms: 3(5 + x) = 2(x + 6) (5 * 3 + x * 3) = 2(x + 6) (15 + 3x) = 2(x + 6) Reorder the terms: 15 + 3x = 2(6 + x) 15 + 3x = (6 * 2 + x * 2) 15 + 3x = (12 + 2x) Solving 15 + 3x = 12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + 3x + -2x = 12 + 2x + -2x Combine like terms: 3x + -2x = 1x 15 + 1x = 12 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + 1x = 12 + 0 15 + 1x = 12 Add '-15' to each side of the equation. 15 + -15 + 1x = 12 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = 12 + -15 1x = 12 + -15 Combine like terms: 12 + -15 = -3 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| 4a^4b^10/16a^7b^4 | | 2x+32+6=x+26 | | 25=4000-16x | | 4x+9-6x+11=3(x+5) | | 7b-7(11-2b)=10 | | p=12+4x | | p=10+2l | | 1/31/2 | | 6x(x+5)=16 | | 6+8a=50+6a-9a | | 12-5u=43 | | p=2l+10 | | x+3x+4x=24 | | 2m+3m-17m=80-m | | 3-3/8X=1/4X | | 1/4(28x-8) | | x+8a=50+ax-9a | | 26/39 | | 1/4X+1/5X=9 | | -3(x+2)=16-2 | | 5-2(x-5)=4x-6 | | 2(2t-5)=20-t | | -28+15-27z=31 | | 1/8y^-5 | | x+8a=50ax-9a | | 5/6X=3-11/12X | | p=x+1+4+4+2+2+x+2+1 | | 6x-3=5x-10x+8 | | 0.7(x+200)=0.75x-225 | | 3(a-2)=6a-(3a+6) | | .2-2=8 | | 3x^2+17x+4=0 |